The Humanitarian Narrative of Pramoedya within the Local Cultural Traditions of Tenganan Pegringsingan - Try Adi Stanaya, I Komang; Swandi, I Wayan; Suteja, I Kt; Garwa, I Ketut (UPT Pusat Penerbitan LP2MPP ISI Bali, 2025)
Pramoedya Ananta Toer is widely known for his humanitarian narratives that place human beings at the center of values. This idea finds its relevance in Tenganan Pegringsingan Village, Bali, which is rich in traditions and a value-based social structure. Although both reflect humanitarian values, there is still limited research linking Pramoedya’s humanism with the cultural practices of indigenous communities such as those in Tenganan. The results of this study reveal three key points. First, there is a connection between Pramoedya’s narrative and the social practices in Tenganan, reflecting the relationship between ideas and the implementation of values. Second, the respect given to traditional leaders is based on their social responsibility, not merely their status. Third, the traditional structure in Tenganan demonstrates collective humanitarian values through mutual cooperation (gotong royong). These findings affirm that Pramoedya’s humanistic values are not only alive in literary works but also manifested within contextual local cultural practices.